2019
DOI: 10.51983/arss-2019.8.3.1603
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Sea Gypsies School Leavers in the Philippines

Abstract: The Sea Gypsies (Badjaos) stride in education since a large number of children not taking part in education programmes. This is due to reasons of an unjustified stigma associated with the Badjao people, which cause them to be discriminated against in school and the employment market. This study ascertained the determinants of Badjao school leavers in Cebu City, Philippines. It employed a descriptive method using the adapted survey questionnaire. Sixty-five respondents were identified using purposive sampling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…This suggested that there may have been few official and informal educational programs available to the Badjaos and that they may have benefited from these programs only occasionally. Because local providers (such as LGUs, CSOs, and some public and state educational institutions) did not take a closer look at the social being, characteristics, and-most importantly-the financial capacity of Badjao families to send and support their children to attend both formal and non-formal education, and educational interventions provided by those local providers appeared to be ineffective (Abelgas, 2019).…”
Section: Results and Discussion I-profile Distribution Of The Badjao ...mentioning
confidence: 99%
“…This suggested that there may have been few official and informal educational programs available to the Badjaos and that they may have benefited from these programs only occasionally. Because local providers (such as LGUs, CSOs, and some public and state educational institutions) did not take a closer look at the social being, characteristics, and-most importantly-the financial capacity of Badjao families to send and support their children to attend both formal and non-formal education, and educational interventions provided by those local providers appeared to be ineffective (Abelgas, 2019).…”
Section: Results and Discussion I-profile Distribution Of The Badjao ...mentioning
confidence: 99%